Islamic Business Ethics and Sustainability: Building a Business Based on Trust and Justice - Jamaluddin, Jamaluddin; Mappaterru, M. Ridwan; Deflyanty S, Putri; Anwar, Anwar (Journal of Islamic Economy, 2025)
This study discusses the relationship between Islamic business ethics and sustainability in building a business based on trust and justice. Using the Systematic Literature Review (SLR) method, this study explores various academic literature from databases such as Scopus, Google Scholar, and ScienceDirect. The analysis was conducted to understand how the principles of Islamic business ethics contribute to sustainability and how aspects of trust and justice support responsible business practices. The results of the study show that Islamic business ethics, which are based on the Qur'an and Hadith, emphasize the principles of honesty, justice, and responsibility in every transaction. This principle not only ensures the economic sustainability of the business but also supports social and environmental welfare. Islam prohibits the practices of usury, gharar, and maysir which are considered detrimental, and encourages profit-sharing systems such as mudharabah and musyarakah. Although there are challenges in implementing Islamic business ethics, such as fierce competition and the dominance of the conventional economic system, solutions that can be applied include increasing Islamic financial literacy and building a transparent and equitable business ecosystem. By implementing these principles, businesses not only gain halal profits but also provide benefits to society and the environment in a sustainable manner